2021
DOI: 10.1002/14651858.cd003737.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for intermittent exotropia

Abstract: Asjes-Tydeman 2006Asjes-Tydeman WL, Groenewoud H, van der Wilt GJ. Timing of surgery for primary exotropia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 109 publications
0
19
0
11
Order By: Relevance
“…We assumed that better fusional function would contribute to a stable postoperative outcome. Further research is needed to explore the role of mechanisms likely associated with exodeviation control to identify the non-surgical therapeutic implications [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that better fusional function would contribute to a stable postoperative outcome. Further research is needed to explore the role of mechanisms likely associated with exodeviation control to identify the non-surgical therapeutic implications [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a lack of consensus on the optimal timing for surgery in children with IXT . Repka et al reported that children who underwent surgery at ages 3 to younger than 5 years had fewer suboptimal outcomes compared with children who underwent surgery at ages 5 to younger than 11 years.…”
Section: Discussionmentioning
confidence: 99%
“…ebate exists regarding the optimal surgical intervention for intermittent exotropia (IXT) in childhood. 1 The initial surgery often involves bilateral lateral rectus recession (BLR) or unilateral lateral rectus recession with medial rectus resection (RR). A Cochrane systematic review, 1 including 2 randomized controlled studies that directly compared BLR with RR, did not find sufficient evidence to support a difference in outcomes between these 2 approaches.…”
mentioning
confidence: 99%
“…A meta-analysis of this issue was conducted by Pang et al [3] who found that PTO achieved better treatment outcomes in terms of near and distant alignment compared to observation, with no evidence that PTO or observation was superior in terms of near stereoacuity. Several controversial aspects of this meta-analysis are worth noting, including the small number of studies (only 2 studies) and cases, the lack of assessment of bias control, and the comparison of only posttreatment distance alignment, near alignment, and near stereopsis, which may have been influenced by baseline values.…”
Section: Discussionmentioning
confidence: 99%